(untitled) (Південний архів (історичні науки), 2021)
The article analyzes the first – pre-revolutionary period of the research process of academic staffs of the universities in Naddnipryanska Ukraine of the second half of the XIX – beginning of the XX century, which allowed to determine the state of study and basic methods, concepts and views of researchers on the development and formation of scientific and pedagogical teams of Naddnipryanska Ukraine, their scientific and professional responsibilities. It is determined that the first initial period – pre-revolutionary – is characterized by the appearance of the first analytical investigations analyzing the University Statute of 1863 and 1884. The works contain materials on the government and the Ministry of Education, the history of Kyiv, Kharkiv and Novorossiysk universities, contains an analysis of some aspects of the organization of educational, scientific work, elimination of student performances, etc. The history of universities, the composition of scientific and pedagogical workers becomes the subject of research of representatives of the scientific intelligentsia of the Naddnipryanska Ukraine, prominent figures of public life. From the second half of the XIX – beginning of the XX century publications appear on certain issues of the organization of university education in the post-reform era and social, economic and social life of representatives of scientific and pedagogical teams. The thesis is substantiated that the pre-revolutionary period of historiography of dissertation research can be called a period of accumulation of historical facts range of sources and issues of historical research on the history of universities of the Naddnipryanska Ukraine in the second half of the XIX – beginning of the XX centuries.